STATISTICAL INTERCONNECTIONS BETWEEN THE INCREMENT OF 7–8-YEAR-OLD BOYS’ PHYSICAL QUALITIES OF DIFFERENT SOMATOTYPES - Zubal, M.; Raitarovska, I. (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2019)
The level of physical development, health, preparation as a criterion for the implementation of a differentiated, individual approach to students in the process of physical education is determined by the current program. However, these criteria are marked by lability, that is, the change in the characteristics under the influence of various external factors, and therefore only partially reflect the individual characteristics of adolescents. On the other hand, indicators are displayed that reflect the different aspects of human life and for a long time remain unchanged – genetic markers, one of which is the somatic type of constitution. Improvement of the physical qualities of boys during 7–8 years became the object of our study. The basis for increasing the efficiency of the process of physical preparation were established by us interconnections between the increment in physical qualities of boys of different somatotypes from 7 to 8 years. The determination of the direction of physical load for the development of physical qualities of boys of different somatotypes at 7–8 years was the goal of our research, in which we solved the following tasks, namely, the study of the peculiarities of the interconnections between the annual increment in the physical qualities of boys of different somatotypes at 7–8 years. The mentioned researches were cross-objective and used various directions and number of tests, and longitudinal single studies alone, which does not contribute to the establishment of regular tendencies and somatotype-specific peculiarities of the physical qualities’ increment, the interconnections between such changes of boys at the stage of 7–8 years. All of the above-mentioned determined the choice of the subject of our research. The results of the experiment, organized by the longitudinal method, made it possible to draw the following conclusions: statistical interconnections between physical qualities in the sensitive period of their development, between these and other qualities under study differ for boys of different somatotypes by the number, magnitude and value of the coefficients of pair correlation, which indicates unequal interdependence of natural development of their physical qualities, and in practice manifests itself in the form of various variants of the transfer of the training effect when using the physical loads of a certain orientation.